Advancing the science of adverse childhood experiences and resilience: A case for global and ecological perspectives - Sherry Hamby; Cristobal Guerra; Edgardo Toro; Cristián Pinto-Cortez (Child Protection and Practice)
Research on adverse childhood experiences and resilience (the process of overcoming trauma) has been dominated by studies originating in wealthy democracies of the global north. We call for more global and ecological approaches not only for documenting the true global burden of childhood adversity, but also for advancing the science of resilience and understanding pathways to overcoming trauma. We identify several forms of trauma that need better consideration in prevalence estimates, including state, political, and institutional violence, crisis migration, climate change and related natural disasters, and global health crises such as the COVID-19 pandemic. We also need more nuanced analyses of culture and place and to recognize that the global south and global north are not monolithic concepts. We offer illustrative examples of how more global, ecological approaches can enhance our understanding of pathways to overcoming even high dosages of childhood adversity. One of the key insights of ACEs research, the dose-response relationship between trauma burden and outcomes, has been extended to research on resilience. Concepts that capture the total “dose” of positive assets and resources (people's resilience portfolios) are showing how people might overcome even high doses of trauma. This work can become more global by including incorporating strengths and healing processes common in collectivist, versus individualistic, cultures. It can become more ecological by recognizing that physical environments—both natural and human-made built aspects—play key roles in resilience. Recognizing the intersectionality among these elements can take us to the next generation of trauma and resilience science.